Rehabilitasi Residen Narkoba Dengan Terapi MeRaBa Di Padepokan Purbo Kayun Bendosewu Talun Blitar: REHABILITATION OF DRUGS RESIDENTS WITH MEABA THERAPY AT PADEPOKAN PURBO KAYUN BENDOSEWU BLITAR - Sulistiani, Nanik - (Balai Diklat Keagamaan Surabaya, 2023)
Spiritual and herbal rehabilitation are considered more effective and more attractive to drug users for rehabilitation compared to seeking help from official healthcare institutions, which may be accompanied by concerns about criminal penalties. This makes it interesting to conduct research to gather information about spiritual and herbal rehabilitation used in the recovery of drug users. The research location is Padepokan Purbo Kayun in Blitar. The research method used is qualitative case study. Data collection techniques involve observation, interviews, and documentation. There are 10 research informants, including 2 from the therapists at Padepokan, 4 from the residents of Padepokan, and 4 from the rehabilitation section of BNNK Blitar. The stages of data analysis include data presentation, data reduction, data verification, and drawing conclusions. The results show that Padepokan Purbo Kayun implements three therapies: MeRaBa (mental, rukyah, and herbal). Additionally, there are lecture sessions on Tuesday and Saturday evenings, and the place receives a high number of visitors (up to 40 people). Among these visitors, some come from the local area, others from different regions, and even from other provinces. An analysis based on social theory for the mental aspect and RCET for the rukyah and herbal aspects agrees that social factors, foot massage therapy, and the consumption of herbal plants play an effective role in the rehabilitation process for residents.